Intravenous pentamidine for Pneumocystis carinii/jiroveci pneumonia prophylaxis in pediatric transplant patients. (25th February 2015) - Clark, Abigail; Hemmelgarn, Trina; Danziger‐Isakov, Lara; Teusink, Ashley
Abstract: SMX/TMP is the current gold standard for prophylaxis against PCP in immunocompromised pediatric patients. Currently, there are several second‐line options for prophylaxis but many, including intravenous (IV) pentamidine, have not been reported to be as effective or as safe as SMX/TMP in the pediatric transplant population. This study is to determine the efficacy and safety of IV pentamidine in preventing PCP in pediatric transplant patients. A retrospective chart review was conducted to evaluate all transplant patients that received at least one dose of IV pentamidine from January 2010 to July 2013. The primary outcome, IV pentamidine efficacy, was evaluated by the incidence of PCP diagnosis for 28 days after the last dose of IV pentamidine if patient was transitioned to another agent for PCP prophylaxis. Patients on IV pentamidine for entire course of PCP prophylaxis were followed at least six months after discontinuation of IV pentamidine. The safety of IV pentamidine was assessed by the incidence of adverse events leading to pentamidine discontinuation. All data were analyzed using descriptive statistics. All transplant patients at CCHMC who had received IV pentamidine were reviewed, and 333 patients met inclusion criteria. The overall incidence of PCP was found to be 0.3% for pediatric transplant patients on pentamidine. Pentamidine was found to be safe, and the incidence of adverse events leading to discontinuation was 6% with the most common reason being tachycardia 2.1%. IV pentamidine is safe and effective as PCP prophylaxis in pediatric transplant patients with a PCP breakthrough rate of 0.3% (1 of 333 patients), and only 20 adverse events led to discontinuation. We recommend that IV pentamidine be considered as a second‐line option in pediatric transplant patients who cannot tolerate SMX/TMP.